A method for producing Li3PO4 particles to obtain olivine-type lithium phosphate-based positive electrode materials
Patent Information
- Application Number
- JP2021035432
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-03-27
- Estimated Expiration
- 2041-03-05
Smart Images

Figure 0007652588000004 
Figure 0007652588000005 
Figure 0007652588000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing Li3PO4 particles to obtain an olivine-type lithium phosphate-based positive electrode material. [Background technology]
[0002] Lithium ion secondary batteries have established their position as high-capacity, lightweight power sources essential for portable electronic devices, electric vehicles, etc. In recent years, with the increase in power consumption due to the high performance of electronic devices, there is a demand for lithium ion secondary batteries with even higher capacities. In order to improve the performance of such batteries, various positive electrode materials have been developed using lithium manganese phosphate and lithium iron phosphate, etc., which have an olivine structure obtained by a process of subjecting them to a hydrothermal reaction.
[0003] Incidentally, most of the lithium phosphate-based positive electrode materials having an olivine structure are obtained from a reaction mixture in which raw material compounds are subjected to a hydrothermal reaction, while the liquid phase separated from the reaction mixture is disposed of as an unnecessary waste liquid. However, a large amount of lithium ions remain in the disposed liquid phase, which results in excessive consumption of the most expensive lithium source among the raw materials, leading to an increase in production costs. For this reason, attempts have been made to recover and reuse the lithium ions remaining in the liquid phase after the hydrothermal reaction.
[0004] For example, Patent Document 1 discloses a method for producing an electrode material, which includes a step of adding an alkali to a solution in which lithium ions separated after a hydrothermal reaction remain until the pH becomes 10.5 or more and 11.8 or less to obtain a solution from which solidified materials have been removed, and a step of generating lithium phosphate by adding a lithium source to the obtained solution, and the like. In this method, unreacted lithium ions generated in the production process of an olivine-based electrode material are recovered as high-purity lithium phosphate. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-47514 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the technology described in Patent Document 1, since the solution to which the lithium source is added has a high pH, a part of the lithium source remains undissolved, and there is a risk that the efficiency of recovering lithium ions cannot be sufficiently achieved. In addition, the particle size of the Li3PO4 particles produced is likely to be large, and there is a risk that an excessive amount of time is required to obtain such particles by solid-liquid separation. This also leads to coarsening of the particle size of the positive electrode active material, and there is a risk that a lithium ion secondary battery produced using this will not be able to exhibit good battery characteristics, so there is still room for improvement.
[0007] Therefore, an object of the present invention is to provide a manufacturing method for obtaining Li3PO4 (trilithium phosphate) particles, which is a useful raw material for manufacturing high-performance olivine-type lithium phosphate-based positive electrode materials, while effectively reusing the lithium ion-containing solution discharged during the manufacture of olivine-type lithium phosphate-based positive electrode materials. [Means for solving the problem]
[0008] Therefore, the present inventors conducted various studies and found a production method that can obtain Li3PO4 particles having a unique shape that enables efficient solid-liquid separation by including a step of adding a specific amount of lithium carbonate or lithium sulfate and sulfuric acid to a lithium ion-containing solution discharged during the production of an olivine-type lithium phosphate-based positive electrode material, subjecting the solution to a bubbling treatment using an inert gas, and then dropping a mixed liquid containing a phosphoric acid compound and an alkali compound.
[0009] That is, the present invention is a method for producing Li3PO4 particles using a solution X discharged when obtaining an olivine-type lithium phosphate-based positive electrode material from a reaction mixture obtained by subjecting raw material compounds to a hydrothermal reaction, the method comprising the steps of: (I) adding lithium carbonate and sulfuric acid, or lithium carbonate, lithium sulfate, and sulfuric acid, to a solution X having a lithium ion content of 1000 mg / L to 20000 mg / L to obtain a mixed solution A having a lithium ion content of 5000 mg / L to 30000 mg / L and a sulfuric acid content of 0.52 mol to 1.00 mol per 1 mol of lithium ion; (II) A step of subjecting the obtained mixture A to a bubbling treatment with an inert gas to obtain a mixture B. (III) A step of adding dropwise a mixed solution C containing a phosphoric acid compound and an alkali compound to the obtained mixed solution B to obtain a mixed solution D having a lithium content of 2.7 mol to 3.3 mol per mol of phosphorus and a content of the alkali compound of 1.6 mol to 2.2 mol per mol of sulfuric acid. (IV) A step of subjecting the obtained mixed liquid D to solid-liquid separation to obtain Li3PO4 particles. The present invention provides a method for producing Li3PO4 particles for obtaining an olivine-type lithium phosphate-based positive electrode material, comprising: Effect of the Invention
[0010] According to the manufacturing method of the present invention, in the process of producing an olivine-type lithium phosphate-based positive electrode material, a specific raw material compound including a lithium compound and the like is subjected to a hydrothermal reaction, and then, while effectively reusing the lithium ion-containing effluent that is separated from the reaction mixture and is to be disposed of, it is possible to easily produce Li3PO4 particles that contain a large number of particles having a unique shape, i.e., a rod-like shape, which can improve the efficiency of solid-liquid separation. In this way, it is possible to obtain Li3PO4 particles that can efficiently separate solid-liquid while efficiently using lithium, a rare and valuable substance, and by using such particles as a raw material, it is possible to obtain an olivine-type lithium phosphate-based positive electrode material that can also exhibit good battery characteristics. [Brief description of the drawings]
[0011] [Figure 1] 1 shows an SEM image of the Li3PO4 particles obtained in Example 1. [Diagram 2]1 shows an SEM image of the Li3PO4 particles obtained in Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below. The method for producing Li3PO4 particles for obtaining an olivine-type lithium phosphate-based positive electrode material of the present invention is a method for producing Li3PO4 particles using a solution X discharged when obtaining an olivine-type lithium phosphate-based positive electrode material from a reaction mixture obtained by subjecting raw material compounds to a hydrothermal reaction, comprising the steps of: The following steps (I) to (IV): (I) adding lithium carbonate and sulfuric acid, or lithium carbonate, lithium sulfate, and sulfuric acid, to a solution X having a lithium ion content of 1000 mg / L to 20000 mg / L to obtain a mixed solution A having a lithium ion content of 5000 mg / L to 30000 mg / L and a sulfuric acid content of 0.52 mol to 1.00 mol per 1 mol of lithium ion; (II) A step of subjecting the obtained mixture A to a bubbling treatment with an inert gas to obtain a mixture B. (III) A step of adding dropwise a mixed solution C containing a phosphoric acid compound and an alkali compound to the obtained mixed solution B to obtain a mixed solution D having a lithium content of 2.7 mol to 3.3 mol per mol of phosphorus and a content of the alkali compound of 1.6 mol to 2.2 mol per mol of sulfuric acid. (IV) A step of subjecting the obtained mixed liquid D to solid-liquid separation to obtain Li3PO4 particles. Equipped with.
[0013] Solution X used in the present invention is an unreacted lithium ion-containing solution discharged when obtaining an olivine-type lithium phosphate-based cathode material from a reaction mixture obtained by subjecting a raw material compound to a hydrothermal reaction, that is, a drainage liquid targeted for so-called waste disposal, and the lithium ion content thereof is 1000 mg / L to 20000 mg / L. In the present invention, by using such solution X, the lithium ion-containing drainage liquid that has once been subjected to the production of an olivine-type lithium phosphate-based cathode material and is targeted for disposal is reused without waste, and a method for producing Li3PO4 particles for obtaining an olivine-type lithium phosphate-based cathode material is realized.
[0014] Here, the olivine-type lithium phosphate-based cathode material may be any material produced from the solid content recovered by separating it from solution X from the obtained reaction mixture after subjecting a predetermined raw material compound to a hydrothermal reaction. Specifically, for example, it is represented by the following formula (X). Li a Mn b Fe c M x PO4 (However, in formula (X), M represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd. a, b, c, and x satisfy 0 < a ≤ 1.2, 0.3 ≤ b ≤ 1.2, 0.2 ≤ c ≤ 1.2, and 0 ≤ x ≤ 0.3, and a + (valence of Mn) × b + (valence of Fe) × c + (valence of M) × x = 3. )
[0015] The olivine-type lithium phosphate-based positive electrode material represented by the above formula (X) contains at least both manganese (Mn) and iron (Fe) as transition metals. That is, in the formula (X), M is one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd and Gd, and is preferably Mg or Zr. For a, 0.6≦a≦1.2 is preferable, 0.65≦a≦1.15 is more preferable, and 0.7≦a≦1.1 is even more preferable. For b, 0.4≦b≦0.8 is preferable, 0.5≦b≦0.8 is more preferable, and 0.7≦b≦0.8 is even more preferable. For c, 0.2≦c≦0.6 is preferable, 0.2≦c≦0.5 is more preferable, and 0.2≦c≦0.3 is even more preferable. With respect to x, 0≦x≦0.2 is preferable, 0≦x≦0.15 is more preferable, and 0≦x≦0.1 is even more preferable.
[0016] Specifically, for example, LiMn 0.3 Fe 0.7 PO4, LiMn 0.7 Fe 0.3 PO4, LiMn 0.9 Fe 0.1 PO4, LiMn 0.8 Fe 0.2 PO4, LiMn 0.75 Fe 0.15 Mg 0.1 PO4, LiMn 0.75 Fe 0.19 Zr 0.03 PO4, LiMn 0.6 Fe 0.4 PO4, LiMn 0.5 Fe 0.5 PO4, Li 1.2 Mn 0.63 Fe 0.27 PO4, Li 0.6 Mn 0.84 Fe 0.36 PO4, etc. Among them, LiMn 0.3 Fe 0.7 PO4, LiMn 0.7 Fe 0.3 PO4, LiMn 0.8 Fe 0.2 PO4, LiMn 0.6 Fe0.4 PO4, Li 1.2 Mn 0.63 Fe 0.27 PO4 or Li 0.6 Mn 0.84 Fe 0.36 PO4 is preferred.
[0017] The production method of the present invention includes, as step (I), a step of adding lithium carbonate and sulfuric acid, or lithium carbonate, lithium sulfate, and sulfuric acid to solution X having a lithium ion content of 1000 mg / L to 20000 mg / L, to obtain mixed solution A having a lithium ion content of 5000 mg / L to 30000 mg / L and a sulfuric acid content of 0.52 mol to 1.00 mol per 1 mol of lithium ions. As described above, in the step (I), the solution X containing a certain amount of lithium ions is used as a starting material, and by adding lithium carbonate or lithium carbonate and lithium sulfate as a lithium source together with sulfuric acid, the solution X, which is a lithium ion-containing waste liquid once subjected to the production of an olivine-type lithium phosphate-based positive electrode material, can be effectively reused.
[0018] From the time when the solution X is recovered until the time when the solution X is subjected to the step (I), it is only necessary to ensure that no impurities are mixed in, and therefore no special storage environment is required. In addition, in order to adjust the lithium ion content of the solution X to the above range, a dilution operation or a concentration operation may be performed by a general method. The lithium ion content of solution X is 1000 mg / L to 20000 mg / L, preferably 2500 mg / L to 20000 mg / L, and more preferably 4000 mg / L to 20000 mg / L, from the viewpoint of increasing the productivity when the obtained Li3PO4 particles are subjected to the production of an olivine-type lithium phosphate-based positive electrode material. Solution X may also contain sulfate ions. For example, the content of sulfate ions in solution X is preferably 3000 mg / L to 150000 mg / L, more preferably 6000 mg / L to 150000 mg / L, and even more preferably 9000 mg / L to 150000 mg / L, from the viewpoint of not unduly interfering with the adjustment of the content of sulfuric acid in mixed solution A by the addition of sulfuric acid, which will be described later.
[0019] The pH of solution X at 25° C. is preferably 6 to 9, more preferably 6 to 8.5, and even more preferably 6 to 8, from the viewpoint of satisfactorily dissolving or dispersing lithium carbonate, lithium sulfate, and sulfuric acid that are subsequently added. The temperature of the solution X is preferably 5°C to 25°C, and more preferably 10°C to 25°C.
[0020] In step (I), lithium carbonate and sulfuric acid, or lithium carbonate, lithium sulfate, and sulfuric acid are added to the solution X without adding a phosphoric acid compound to obtain a mixed solution A having a lithium ion content of 5000 mg / L to 30000 mg / L and a sulfuric acid content of 0.52 mol to 1.00 mol per mol of lithium ion, that is, a mixed solution A in which lithium carbonate, or lithium carbonate and lithium sulfate are completely dissolved. In this way, when obtaining the mixed solution A, either lithium carbonate alone or lithium carbonate and lithium sulfate are used in combination as a lithium source to be added to the solution X, and lithium carbonate is always used. This allows the pH environment to be adjusted to a low range, while promoting the dissolution of lithium carbonate and lithium sulfate, while gasifying or insolubilizing the carbonic acid (dissolved carbonic acid) derived from the added lithium carbonate that is excessively dissolved in the solution, and coupled with the bubbling treatment in the step (II) described below, it is possible to obtain Li3PO4 particles with a unique shape that contains many rod-shaped particles and can improve the efficiency of solid-liquid separation. In addition, the addition of sulfuric acid to solution X makes it easier to treat the effluent compared to the case of adding nitric acid, organic acid, hydrochloric acid, etc., and can effectively avoid the generation of repellent components. Furthermore, by adding a phosphoric acid compound in the step (IV) described below without adding a phosphoric acid compound in the step (I), it is possible to efficiently and simply manufacture Li3PO4 particles. In this way, in the present invention, Li3PO4 particles having a unique shape can be efficiently obtained by using carbonate derived from lithium carbonate.
[0021] In this specification, "lithium carbonate, or a mixed solution in which lithium carbonate and lithium sulfate are completely dissolved" means that the added lithium carbonate or lithium sulfate is completely dissolved in the solvent, and no suspended matter or precipitate is generated in the mixed solution, making it a highly transparent mixed solution, a liquid substance different from a so-called slurry. "Carbonate derived from lithium carbonate (dissolved carbonic acid)" means carbonic acid present in a dissolved state in the mixed solution, and is CO3 2- or HCO3 - It is a general term for ions such as those listed above, and dissolved carbon dioxide (CO2).
[0022] The amount of sulfuric acid added to solution X may be an amount such that the content of sulfuric acid in the resulting mixed solution A is 0.52 mol to 1.00 mol per 1 mol of lithium ion in the mixed solution A, and from the viewpoint of efficiently removing dissolved carbon dioxide, the amount is preferably 0.52 mol to 0.95 mol, and more preferably 0.52 mol to 0.90 mol. From the viewpoint of efficiently removing dissolved carbon dioxide, the mass ratio of the amount of sulfuric acid to the amount of lithium carbonate added to solution X (sulfuric acid / lithium carbonate) is preferably 1.2 to 4.8, more preferably 1.2 to 4.0, and even more preferably 1.2 to 3.2. From the viewpoint of efficiently removing dissolved carbon dioxide, the amount of lithium carbonate added is preferably 50% by mass or more, more preferably 75% by mass or more, and even more preferably 100% by mass, of the total amount of lithium carbonate and lithium sulfate added being 100% by mass.
[0023] The content of lithium ions in the mixed solution A obtained in the step (I) is 5000 mg / L to 30000 mg / L, preferably 7500 mg / L to 27500 mg / L, and more preferably 10000 mg / L to 25000 mg / L, from the viewpoint of increasing the productivity of the Li3PO4 particles. That is, the content of lithium ions in the mixed solution A is greater than the content of lithium ions in the solution X, and when lithium carbonate is used alone as the lithium source, the amount of lithium ions released from the lithium carbonate should be taken into consideration so that the lithium ions are added to the mixed solution A in such an amount. When lithium carbonate and lithium sulfate are used in combination as the lithium source, these lithium sources should be added in consideration of the amounts of lithium ions released from both lithium carbonate and lithium sulfate.
[0024] Regarding the order of adding lithium carbonate and sulfuric acid, or lithium carbonate, lithium sulfate, and sulfuric acid to solution X, it is preferable to add lithium carbonate first, or lithium carbonate and lithium sulfate first, and then sulfuric acid, from the viewpoint of sufficiently and effectively promoting the dissolution of lithium carbonate. Here, before adding sulfuric acid, lithium carbonate or lithium carbonate and lithium sulfate may be added in advance to solution X, which may be stirred. The stirring time is preferably 5 minutes to 300 minutes, and more preferably 10 minutes to 180 minutes.
[0025] The pH of the mixed solution A obtained in step (I) at 25°C is preferably 0.5 to 5, more preferably 1 to 5, and even more preferably 1.5 to 5, from the viewpoint of leaving the dissolved carbon dioxide in the form of H2CO3 and effectively and efficiently removing the dissolved carbon dioxide from the mixed solution by bubbling treatment with an inert gas in the subsequent step (II). The temperature of the mixed liquid A is preferably 25°C to 50°C, and more preferably 30°C to 50°C.
[0026] The manufacturing method of the present invention includes, as step (II), a step of subjecting the mixed liquid A obtained in step (I) to a bubbling treatment with an inert gas to obtain a mixed liquid B. By subjecting the mixed liquid A to a bubbling treatment with an inert gas in this manner, the inert gas is blown into the mixed liquid A, and the dissolved carbon dioxide remaining in the mixed liquid A, particularly the dissolved carbon dioxide remaining in the form of CO2, can be effectively and efficiently removed. Therefore, as a manufacturing method, while simplifying the process, it is possible to efficiently obtain Li3PO4 particles having a unique shape that can improve the efficiency of solid-liquid separation.
[0027] The inert gas that can be used is preferably nitrogen, argon or helium, and more preferably nitrogen. From the viewpoint of sufficiently and effectively removing dissolved carbon dioxide, the total amount of inert gas injected in the bubbling treatment is preferably 0.5 to 15, more preferably 1 to 15, and even more preferably 2 to 15, in terms of the ratio of the total volume of the injected inert gas to the volume of mixed liquid A (total volume of inert gas / volume of mixed liquid A). From the same viewpoint, the time for the bubbling treatment is preferably 10 minutes to 300 minutes, more preferably 20 minutes to 240 minutes, and further preferably 30 minutes to 180 minutes.
[0028] The pH of the mixed solution B obtained in the step (II) at 25° C. is acidic, specifically, preferably 0.5 to 5, more preferably 1 to 5, and further preferably 1.5 to 5. The temperature of the mixed liquid B is preferably 20°C or higher, and more preferably 25°C to 50°C.
[0029] The production method of the present invention includes, as step (III), adding dropwise mixed solution C containing a phosphoric acid compound and an alkali compound to mixed solution B obtained in step (II) to obtain mixed solution D having a lithium content of 2.7 mol to 3.3 mol per mol of phosphorus and an alkali compound content of 1.6 mol to 2.2 mol per mol of sulfuric acid. That is, in the present invention, in step (I), lithium carbonate or lithium sulfate and sulfuric acid are added without adding a phosphoric acid compound, while in step (III), mixed solution C containing a phosphoric acid compound is added dropwise.
[0030] In this way, by dropping mixed solution C containing an alkaline compound together with a phosphoric acid compound, the acidic mixed solution B is neutralized while the Li ions and PO4 ions in the mixed solution appropriately control the nucleation reaction of Li3PO4 particles, forming Li3PO4 particles with a unique shape that contains many rod-shaped particles and can improve the efficiency of solid-liquid separation. 2- It is also possible to prevent a decrease in the purity of the Li3PO4 particles and contamination caused by impurities such as ions.
[0031] The mixed liquid C to be dropped into the mixed liquid B contains a phosphoric acid compound and an alkaline compound. Examples of the phosphoric acid compound include orthophosphoric acid (H3PO4, phosphoric acid), metaphosphoric acid, pyrophosphoric acid, triphosphoric acid, tetraphosphoric acid, ammonium phosphate, ammonium hydrogen phosphate, etc. Among them, it is preferable to use phosphoric acid, and it is preferable to use it as an aqueous solution with a concentration of 40 to 90 mass % from the viewpoint of enabling an appropriate nucleation reaction to obtain Li3PO4 particles having a unique shape. The alkaline compound may be one or more selected from sodium hydroxide (alkali ion = sodium ion) and potassium hydroxide (alkali ion = potassium ion). Among them, it is preferable to use sodium hydroxide from the viewpoint of improving the recovery rate of Li3PO4 particles and the battery characteristics of a lithium ion battery obtained by using an olivine-type lithium phosphate-based positive electrode material produced from the recovered Li3PO4 particles. Such an alkaline compound may be a solid (granular or flake-like) or may be an alkaline solution such as an aqueous solution, and is preferably an alkaline aqueous solution.
[0032] The content of the phosphate compound in the mixed solution C may be an amount that results in a phosphorus content in the mixed solution C of 10,000 ppm to 60,000 ppm, and more preferably an amount that results in a phosphorus content in the mixed solution C of 15,000 ppm to 55,000 ppm. The content of the alkaline compound in the mixed solution C may be 2.7 to 3.6 moles of the alkaline compound per mole of phosphoric acid in the mixed solution C, and more preferably 2.9 to 3.3 moles.
[0033] In preparing such a mixed solution C, from the viewpoint of suppressing precipitation of the alkaline phosphate by the buffering action, specifically, it is preferable to add the alkaline solution dropwise to the phosphoric acid compound and then stir the mixture. The dropping speed of the alkaline solution is preferably 2 to 50 minutes, more preferably 5 to 30 minutes, calculated as the time required to drop the entire amount of the alkaline solution onto the phosphoric acid compound. It is preferable to stir the phosphoric acid compound while dropping the alkaline solution. The stirring time for the phosphoric acid compound when the alkaline solution is dropped is preferably 5 to 120 minutes, and more preferably 10 to 60 minutes.
[0034] The temperature of the mixed liquid C is preferably 40°C to 70°C, and more preferably 45°C to 65°C. The pH of the mixed solution C at 25° C. is preferably 12-14, more preferably 12-13.5, and further preferably 12-13.
[0035] Next, in step (III), the obtained mixed liquid C is dropped into mixed liquid B to obtain mixed liquid D. By dropping mixed liquid C containing a phosphoric acid compound and an alkali compound into mixed liquid B, the nucleation reaction of Li3PO4 particles can be appropriately controlled, and Li3PO4 particles having high purity and a unique shape that can be efficiently separated into solid and liquid can be efficiently produced.
[0036] From the viewpoint of appropriately controlling the nucleation reaction of Li3PO4 particles having a unique shape, the dropping speed of mixed liquid C is preferably 10 to 100 minutes, more preferably 10 to 30 minutes, calculated as the time required to drop the entire amount of mixed liquid C into mixed liquid B. It is preferable to stir mixed liquid B while dropping mixed liquid C. In addition, after adding mixed liquid C dropwise to mixed liquid B, the mixture is preferably stirred. Specifically, the stirring time is preferably 10 to 60 minutes, and more preferably 10 to 30 minutes.
[0037] The content of lithium in the mixed solution D is 2.7 mol to 3.3 mol, preferably 2.7 mol to 3.2 mol, and more preferably 2.7 mol to 3.1 mol, per mol of phosphorus in the mixed solution D. The content of the alkali compound in the mixed solution D is 1.6 mol to 2.2 mol, preferably 1.7 mol to 2.1 mol, and more preferably 1.8 mol to 2.0 mol, relative to 1 mol of sulfuric acid in the mixed solution D. Mixed liquid C containing a phosphoric acid compound and an alkaline compound may be added dropwise to mixed liquid B so that the lithium content and the alkaline compound content in mixed liquid D are within the above ranges.
[0038] The temperature of the mixed liquid D obtained in the step (III) is preferably 30°C to 70°C, more preferably 40°C to 60°C. The pH of the mixed solution D at 25° C. is preferably 9 to 12, and more preferably 9 to 11.5.
[0039] The manufacturing method of the present invention includes, as step (IV), a step of subjecting the mixed liquid D obtained in step (III) to solid-liquid separation to obtain Li3PO4 particles. Since the mixed liquid D contains precipitated Li3PO4 particles having high purity and a unique shape that can improve the efficiency of solid-liquid separation, these can be precipitated and recovered in step (IV). Examples of devices used for solid-liquid separation include a filter press machine, a centrifugal filter machine, and a vacuum filter machine. Among them, it is preferable to use a filter press machine from the viewpoint of efficiently obtaining Li3PO4 particles.
[0040] The obtained Li3PO4 particles (cake) is preferably further dried, preferably by constant temperature drying, freeze drying or vacuum drying.
[0041] The manufacturing method of the present invention can obtain fine Li3PO4 particles containing many particles with a unique shape, i.e., rod-like shape, which can appropriately control the nucleation reaction of Li3PO4 particles and can improve the efficiency of solid-liquid separation. Such Li3PO4 particles have high filterability that can effectively reduce the amount of water used in washing, so that the washing time can be shortened and the efficiency of solid-liquid separation can be effectively improved. In addition, the Li3PO4 particles obtained by the manufacturing method of the present invention can also exhibit good battery characteristics, making them useful raw materials for manufacturing high-performance olivine-type lithium phosphate-based positive electrode materials.
[0042] Specifically, the average aspect ratio of the obtained Li3PO4 particles is preferably 3 to 6, more preferably 3 to 5.5, and even more preferably 3 to 5, from the viewpoint of containing many rod-shaped particles and improving filterability. The average aspect ratio of Li3PO4 particles means the average aspect ratio obtained by randomly selecting 200 Li3PO4 particles, measuring the maximum diameter in the long axis direction and the maximum diameter in the direction perpendicular to the long axis direction, and calculating the average of these values. The aspect ratio is the ratio of the long axis length to the short axis length.
[0043] In addition, the average particle size (D 50 ) is preferably 1 μm to 20 μm, more preferably 4 μm to 20 μm, and further preferably 7 μm to 20 μm. The average particle size of Li3PO4 particles (D 50 ) means the cumulative 50% particle size on a volume basis measured by a laser diffraction / scattering method. The resulting Li3PO4 particles preferably have a BET specific surface area of 1 m 2 / g or more, more preferably 3m 2 / g or more, preferably 15m 2 / Below is.
[0044] From the viewpoint of imparting a unique shape and enabling particle refinement, it is preferable that the Li3PO4 particles obtained by the production method of the present invention do not contain carbon derived from lithium carbonate or lithium sulfate that was not fully dissolved in step (I) or carbon derived from dissolved carbonic acid that was not fully removed during the process. Specifically, the amount of such remaining carbon is preferably 0.3 mass% or less, more preferably 0.2 mass% or less, in the Li3PO4 particles. The amount of carbon remaining in the Li3PO4 particles can be confirmed using a carbon-sulfur analyzer (EMIA-220V2, manufactured by Horiba, Ltd.).
[0045] When the Li3PO4 particles obtained by the production method of the present invention are used as a raw material to obtain, for example, an olivine-type lithium phosphate-based positive electrode material represented by the above formula (X), the following steps (i) to (ii) are carried out: (i) a step of adding and mixing a metal source containing an iron compound and a manganese compound and which may also contain a metal (M) compound (M represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd) to the obtained Li3PO4 particles, and then subjecting the mixture to a hydrothermal reaction to obtain a reaction mixture. (ii) A step of separating the solution containing unreacted Li ions from the reaction mixture obtained in step (i) to obtain an olivine-type lithium phosphate-based positive electrode material. The manufacturing method can be obtained by the method.
[0046] The above-mentioned step (i) is a step of adding and mixing a metal source that contains an iron compound and a manganese compound and may also contain a metal (M) compound (M represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd) to the Li3PO4 particles obtained by the manufacturing method of the present invention, and then subjecting the mixture to a hydrothermal reaction to obtain a reaction mixture.
[0047] The iron compound that can be used may be a divalent iron compound or a hydrate thereof, for example, halides such as iron halides, sulfates such as iron sulfate, organic acid salts such as iron oxalate and iron acetate, and hydrates thereof. Among them, it is preferable to use iron sulfate or a hydrate thereof from the viewpoint of improving the battery properties or from the viewpoint of further effectively utilizing the effluent obtained in step (i) in the production method of the present invention.
[0048] The manganese compound that can be used may be a divalent manganese compound or a hydrate thereof, for example, a halide such as manganese halide, a sulfate such as manganese sulfate, an organic acid salt such as manganese oxalate or manganese acetate, and a hydrate thereof. Among them, it is preferable to use manganese sulfate or a hydrate thereof from the viewpoint of improving the battery properties or from the viewpoint of further effectively utilizing the effluent obtained in step (i) as a part of the solution X in the production method of the present invention.
[0049] The metal compound other than the iron compound and the manganese compound may be any compound containing M in formula (X) as a metal (M represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd), and may be, like the iron compound and the manganese compound, a halide, a sulfate, an organic acid salt, or a hydrate thereof. Among them, from the viewpoint of improving the battery properties, it is preferable to use a sulfate or a hydrate thereof, and it is more preferable to use a metal (M) sulfate in which M is Mg or Zr.
[0050] The molar ratio of the iron compound and the manganese compound used (manganese compound:iron compound) is preferably 99:1 to 30:70, more preferably 95:5 to 40:60, and further preferably 90:10 to 50:50.
[0051] The Li3PO4 particles obtained by the production method of the present invention are mixed with water to form a Li3PO4-containing mixture, to which a metal source such as a metal compound containing the iron compound and manganese compound is added and mixed to produce a mixture for subjecting to a hydrothermal reaction. The order of addition of such metal sources is not particularly limited. It is preferable to stir the Li3PO4-containing mixture before mixing the metal source into the Li3PO4-containing mixture. The stirring time of the Li3PO4-containing mixture is preferably 1 to 10 minutes, more preferably 2 to 8 minutes. This stirring makes it possible to obtain a Li3PO4-containing mixture with uniformity.
[0052] Next, the metal source is added to the Li3PO4-containing mixture and mixed. The metal source is mixed while stirring the Li3PO4-containing mixture. The pH of the mixture is preferably 3.5 to 8, more preferably 4 to 7. The total amount of these metal sources added is preferably 0.90 to 1.10 mol, more preferably 0.95 to 1.05 mol, relative to 1 mol of Li3PO4 contained in the mixture.
[0053] The mixture containing Li3PO4 and a metal source is subjected to a hydrothermal reaction. This produces a compound that becomes an olivine-type lithium phosphate-based positive electrode material, and a reaction mixture containing the compound can be obtained. The amount of water used in producing the mixture containing Li3PO4 and a metal source is preferably 10 mol to 90 mol, more preferably 20 mol to 70 mol, relative to 1 mol of Li3PO4 contained in the mixture, from the viewpoints of the solubility of the metal source, ease of stirring, and synthesis efficiency. In addition, an antioxidant may be added to the mixture to be subjected to the hydrothermal reaction, if necessary. As such an antioxidant, sodium sulfite (Na2SO3), sodium hydrosulfite (Na2S2O4), aqueous ammonia, etc. can be used. The amount of the antioxidant added is preferably 0.01 mol to 1 mol, more preferably 0.03 mol to 0.5 mol, per mol of the metal source, from the viewpoint of preventing inhibition of the formation of a compound that becomes an olivine-type lithium phosphate-based positive electrode material due to excessive addition.
[0054] The hydrothermal reaction may be carried out at a temperature of 100° C. or higher, preferably 130° C. to 180° C. Such a hydrothermal reaction is preferably carried out in a pressure-resistant vessel, and when the reaction is carried out at 130° C. to 180° C., the pressure is preferably 0.3 MPa to 0.9 MPa, and when the reaction is carried out at 140° C. to 160° C., the pressure is preferably 0.3 MPa to 0.6 MPa. The hydrothermal reaction time is preferably 0.5 hours to 24 hours, more preferably 3 hours to 12 hours.
[0055] The above step (ii) is a step of obtaining an olivine-type lithium phosphate-based positive electrode material by separating a solution containing unreacted Li ions from the reaction mixture containing the olivine-type lithium phosphate-based positive electrode material obtained in the above step (i). The device used for separating the solution containing unreacted Li ions from the reaction mixture, that is, for solid-liquid separation, can be the same as that described above, and from the viewpoint of efficiently obtaining the positive electrode material, it is preferable to use a filter press machine. Furthermore, the obtained positive electrode material is preferably washed with water. When washing the positive electrode material with water, 3 to 20 parts by mass of water is preferably used, and 5 to 15 parts by mass of water is more preferably used, per 1 part by mass of the positive electrode material. Since the washing water contains unreacted Li ions washed away from the positive electrode material, the entire amount of the washing water can be recovered and used as the solution X in step (I) of the present invention together with the solution obtained by solid-liquid separation. In order to efficiently recover the washing water, it is preferable to perform washing and solid-liquid separation using a filter press machine. The recovered water does not need to be contaminated with impurities until it is used in step (I), and does not require a special storage environment. In addition, in order to adjust the Li ion concentration in the recovered water, a dilution operation or a concentration operation can be performed by a general method.
[0056] The olivine-type lithium phosphate-based positive electrode material separated and recovered in step (ii) is dried, if necessary, by spray drying, vacuum drying, freeze drying, or the like.
[0057] The average particle size of such an olivine-type lithium phosphate-based positive electrode material is preferably 10 nm to 200 nm, and more preferably 30 nm to 150 nm.
[0058] The obtained olivine-type lithium phosphate-based positive electrode material is preferably supported by carbon and then calcined to obtain a positive electrode active material. Carbon support may be performed by adding a carbon source such as glucose, fructose, polyethylene glycol, polyvinyl alcohol, carboxymethyl cellulose, saccharose, starch, dextrin, citric acid, and water to the olivine-type lithium phosphate-based positive electrode material in a conventional manner, and then calcining. The calcination conditions are preferably 400°C or higher, preferably 400°C to 800°C, under an inert gas atmosphere or reducing conditions, for 10 minutes to 3 hours, preferably 0.5 hours to 1.5 hours. This treatment can provide a positive electrode active material in which carbon is supported on the particle surface of the positive electrode material. The amount of carbon source used is preferably 3 parts by mass to 15 parts by mass as the carbon contained in the carbon source, and more preferably 5 parts by mass to 10 parts by mass as the carbon contained in the carbon source, relative to 100 parts by mass of the positive electrode material.
[0059] In addition to the above treatment, a method of crushing / composite-mixing the mixture containing the obtained olivine-type lithium phosphate-based positive electrode material and the conductive carbon material may be used as a treatment for supporting carbon on the surface of the particles. By carrying out such a treatment, a positive electrode active material in which the positive electrode material and the conductive carbon material are combined can be formed, and the conductivity can be further increased.
[0060] The conductive carbon material used in the pulverization / composite / mixing treatment is preferably carbon black, and more preferably acetylene black or ketjen black. The amount of the conductive carbon material added is preferably 0.5 to 15 parts by mass, more preferably 2 to 10 parts by mass, in terms of carbon atom, relative to 100 parts by mass of the positive electrode material, from the viewpoints of good discharge capacity and economic efficiency.
[0061] The mixture of the olivine-type lithium phosphate-based positive electrode material and the conductive carbon material is subjected to a dry grinding / composite / mixing process, in which a small amount of diethylene glycol, ethanol, or the like may be added as an auxiliary agent.
[0062] The equipment for carrying out the grinding / compounding / mixing processes may be a normal ball mill, but a planetary ball mill capable of rotating and revolving (manufactured by Fritsch) is preferable, and any equipment capable of carrying out mechanochemical action / compounding processes on the material to be treated may be used, such as a Nobilta (manufactured by Hosokawa Micron Corporation), a Multipurpose Mixer (manufactured by Nippon Coke and Engineering Co., Ltd.), or a Hybridizer (manufactured by Nara Kikai Co., Ltd.).
[0063] The container of the device used in the planetary ball mill may be made of steel, stainless steel, or nylon, and the inner wall may be made of alumina bricks, magnetic material, natural silica stone, rubber, or urethane. The balls used may be alumina balls, natural silica stone, iron balls, or zirconia balls. The size of the balls is preferably 0.1 mm to 20 mm, and more preferably 0.5 mm to 5 mm. The amount of balls filled is preferably such that the ball filling volume occupies 5 to 50% of the internal volume of the mill used. Mixing using a planetary ball mill is carried out, for example, under conditions of revolution of 50 rpm to 800 rpm and rotation of 100 rpm to 1,600 rpm, preferably for 5 minutes to 24 hours, more preferably for 0.5 hours to 6 hours, and even more preferably for 1 hour to 3 hours.
[0064] The positive electrode active material obtained by compounding carbon on the surface of the olivine-type lithium phosphate-based positive electrode material as described above is preferably calcined under an inert gas atmosphere or under reducing conditions, preferably at 500°C to 800°C for 10 minutes to 24 hours, more preferably at 600°C to 700°C for 0.5 hours to 3 hours. This treatment makes it possible to obtain a positive electrode active material in which carbon is further firmly supported on the surface of the positive electrode material. The apparatus used for calcination is not particularly limited as long as it is capable of adjusting the calcination atmosphere and temperature, and any of the batch type, continuous type, and heating type (indirect or direct) can be used. Examples of such apparatus include tubular electric furnaces such as externally heated kilns and roller hearths.
[0065] Next, a lithium ion secondary battery containing the obtained olivine-type lithium phosphate-based positive electrode material will be described. The lithium ion secondary battery to which such a positive electrode material can be applied is not particularly limited as long as it essentially comprises a positive electrode, a negative electrode, an electrolyte, and a separator.
[0066] Here, the negative electrode is not particularly limited in terms of its material composition, and any known material composition can be used as long as it can absorb lithium ions during charging and release them during discharging. For example, lithium metal, graphite, amorphous carbon, and other carbon materials are used. It is preferable to use an electrode formed of an intercalation material capable of electrochemically absorbing and releasing lithium, particularly a carbon material.
[0067] The electrolyte solution is a solution of a supporting salt dissolved in an organic solvent. The organic solvent is not particularly limited as long as it is an organic solvent that is usually used in electrolytes of lithium ion secondary batteries, and examples of the organic solvent that can be used include carbonates, halogenated hydrocarbons, ethers, ketones, nitriles, lactones, and oxolane compounds.
[0068] The supporting salt is not particularly limited in type, but is preferably at least one of inorganic salts selected from LiPF6, LiBF4, LiClO4, and LiAsF6, derivatives of such inorganic salts, organic salts selected from LiSO3CF3, LiC(SO3CF3)2, LiN(SO3CF3)2, LiN(SO2C2F5)2, and LiN(SO2CF3)(SO2C4F9), and derivatives of such organic salts.
[0069] The separator serves to electrically insulate the positive and negative electrodes and to retain the electrolyte, and may be, for example, a porous synthetic resin film, particularly a porous film of a polyolefin polymer (polyethylene, polypropylene). EXAMPLES
[0070] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples.
[0071] [Example 1] Li3PO4 particles were produced according to the conditions shown in Tables 1-2. Specifically, solution X contains 10,000 mg / L of lithium ions and 69,000 mg / L of sulfate ions. 1 0.59 kg of Li2CO3 (manufactured by FMC, purity 99%) and 0.98 kg of sulfuric acid (manufactured by Kurita Co., Ltd., purity 95%) were added to 10 L (pH = 7.2 at 25 °C, temperature 20 °C) to obtain mixed solution A. 1 (Mixture A 1 The mixture was prepared as follows: sulfuric acid content per 1 mole of Li ion in the mixture = 0.55 moles, Li ion content = 20,000 mg / L, pH = 4.2 at 25°C, temperature = 30°C). 1 Stir for 10 minutes, then add mixed solution A while stirring. 1 Nitrogen bubbling treatment (total volume of nitrogen / mixture A) 1 (volume = 4) for 30 minutes, and mixed solution B 1 (pH=4.2 at 25°C, temperature 25°C). Separately, 5 L of water and 1.35 kg of phosphoric acid (Shimonoseki Mitsui Chemicals, Inc., 75%) were mixed, and then 2.75 kg of NaOH solution (Kurita Corporation, purity 48%) was added dropwise while stirring and mixing, and then the mixture was stirred for another 10 minutes to obtain mixed solution C. 1 (NaOH content per mole of phosphoric acid = 3.2 moles, pH = 13 at 25°C, temperature 60°C) was obtained.
[0072] Next, Mixture B 1 Mixture C 1 While dripping (dropping rate = mixed solution C 1 The entire amount is mixed solution B. 1 The time required for dropping the mixture into the flask was 12.5 minutes. The mixture was then stirred for another 10 minutes to obtain the mixture D. 1 (Li content per mole of P = 2.94 moles, NaOH content per mole of sulfuric acid = 2.0 moles) was obtained. Mixture D 1 A portion of the mixture was taken and the particle size distribution was measured. 1 Particle size distribution of Li3PO4 aggregates contained in 50 was 9 μm. The resulting mixture D 110 L of the mixture was filtered using a vacuum filter, and the filtrate was removed. Next, 500 ml of washing water was added to the solid matter obtained, and the time until the solid matter could be filtered was measured. The conductivity of the filtrate after filtration was measured, and the filtrate was then stored in a separate container. This washing operation was repeated until the conductivity of the filtrate after filtration was 8 mS / cm or less. After washing, the resulting Li3PO4 cake was freeze-dried to obtain Li3PO4 particles. 1 The carbon content was below the detection limit. The Li3PO4 particles obtained were single-phase and showed an X-ray diffraction pattern corresponding to the space group Pmnbs. The SEM image of the Li3PO4 particles obtained is shown in Figure 1, and the physical properties of the Li3PO4 particles are shown in Table 3.
[0073] [Example 2] According to the conditions shown in Tables 1 and 2, and solution X 1 Add 0.59 kg of Li2CO3 and 0.88 kg of sulfuric acid to 10 L (pH = 7.2 at 25 °C, temperature 20 °C) to obtain mixed solution A. 2 (Mixture A 2 The same procedure as in Example 1 was carried out to obtain Li3PO4 particles, except that the sulfuric acid content per 1 mole of Li ions in the solution was 0.52 moles, the pH at 25°C was 4.8, and the temperature was 30°C.
[0074] [Example 3] According to the conditions shown in Tables 1 and 2, 5 L of water and 1.41 kg of phosphoric acid were mixed, and then 2.75 kg of NaOH solution was added dropwise while stirring and mixing, and then the mixture was stirred for another 10 minutes to obtain mixed solution C. 3 The same procedure as in Example 1 was carried out except that the aqueous solution was prepared in a manner similar to that in Example 1 (NaOH content per mole of phosphoric acid=3.05 moles, pH=12 at 25° C., temperature=60° C.). Li3PO4 particles were obtained.
[0075] [Example 4] According to the conditions shown in Tables 1 and 2, 5 L of water and 1.35 kg of phosphoric acid were mixed, and then 2.49 kg of NaOH solution was added dropwise while stirring and mixing, and then the mixture was stirred for another 10 minutes to obtain mixed solution C. 4Li3PO4 particles were obtained in the same manner as in Example 1, except that the following was prepared: (NaOH content per mole of phosphoric acid=2.9 moles, pH=12 at 25° C., temperature=55° C.).
[0076] [Comparative Example 1] Without preparing mixed solution C containing a phosphate compound and an alkali compound in advance, mixed solution D was prepared by sequentially adding an alkali compound and a phosphate compound to mixed solution B, and Li3PO4 particles were obtained according to the conditions shown in Tables 1 and 2. Specifically, solution X contains 12,000 mg / L of lithium ions and 83,000 mg / L of sulfate ions. 1 0.73 kg of Li2CO3 (manufactured by FMC, purity 99%) and 1.27 kg of sulfuric acid (manufactured by Kurita Co., Ltd., purity 95%) were added to 10 L (pH = 6.7 at 25 °C, temperature 20 °C) to obtain mixed solution A. x1 (Mixture A x1 The mixture was prepared as follows: sulfuric acid content per 1 mole of Li ion in the mixture = 0.57 moles, Li ion content = 24,000 mg / L, pH = 3.9 at 25°C, temperature 30°C). x1 Stir for 10 minutes, then add mixed solution A while stirring. x1 Nitrogen bubbling treatment (total volume of nitrogen / mixture A) 1 (volume = 5) for 30 minutes, and mixed solution B x1 (pH=3.9 at 25° C., temperature 25° C.). The resulting mixture B x1 While dripping 4.29 kg of NaOH solution (manufactured by Kurita Corporation, purity 48%) into the 1 The amount of Na ions added per mole of lithium ions in the solution is 1.4 moles.) Stir and mix the solution, then stir for another 10 minutes to obtain mixed solution C. x1 (pH at 25°C = 14; not measurable, temperature 45°C) was obtained.
[0077] Next, mixed solution C x1 While stirring, add mixed solution C. x1 1.60 kg of phosphoric acid (manufactured by Mitsui Chemicals, Shimonoseki, 75%) (mixture C 1The amount of H3PO4 added per 1 mole of Li ion in the solution (=0.33 moles) was added dropwise while stirring and mixing, and the mixture was stirred for another 10 minutes to obtain mixed solution D. x1 (pH=12.5 at 25°C, temperature 50°C). The resulting mixture D x1 From the above, Li3PO4 particles were obtained in the same manner as in Example 1.
[0078] [Comparative Example 2] According to the conditions shown in Tables 1 and 2, and solution X 1 Add 0.59 kg of Li2CO3 and 0.82 kg of sulfuric acid to 10 L (pH = 7.2 at 25 °C, temperature 20 °C) to obtain mixed solution A. x2 (Mixture A x2 The same procedure as in Example 1 was carried out to obtain Li3PO4 particles, except that the sulfuric acid content per 1 mole of Li ions in the solution was 0.50 moles, the pH at 25°C was 5.8, and the temperature was 30°C.
[0079] [Comparative Example 3] According to the conditions shown in Tables 1 and 2, and mixed solution A 1 Li3PO4 particles were obtained in the same manner as in Example 1, except that the nitrogen bubbling treatment was not performed on the Li3PO4 particles.
[0080] [Comparative Example 4] According to the conditions shown in Tables 1 and 2, 5 L of water and 1.65 kg of phosphoric acid were mixed, and then 2.74 kg of NaOH solution was added dropwise while stirring and mixing, and then the mixture was stirred for another 10 minutes to obtain mixed solution C. x4 The same procedure as in Example 1 was carried out except that the aqueous solution was prepared in a manner similar to that in Example 1 (NaOH content per mole of phosphoric acid=2.6 moles, pH=11 at 25° C., temperature=60° C.). Li3PO4 particles were obtained.
[0081] [Comparative Example 5] According to the conditions shown in Tables 1 and 2, 5 L of water and 1.35 kg of phosphoric acid were mixed, and then 1.98 kg of NaOH solution was added dropwise while stirring and mixing, and then the mixture was stirred for another 10 minutes to obtain mixed solution C. x5The same procedure as in Example 1 was carried out except that the aqueous solution was prepared in a manner similar to that in Example 1 (NaOH content per mole of phosphoric acid=2.3 moles, pH=11 at 25° C., temperature=50° C.). Li3PO4 particles were obtained.
[0082] 《Evaluation of Li3PO4 particle filterability》 -Filtration time measurement 10 L of the mixture D obtained in each step was sampled, and the time required for solid-liquid separation into a cake and a filtrate by suction filtration was measured. The obtained filtrate was discarded.
[0083] -Measurement of washing water volume 500 ml of water was added to the cake obtained when measuring the filtration time, and then suction filtration was performed to obtain a filtrate. The conductivity of the obtained filtrate was then measured. After measuring the conductivity, the filtrate was removed and the entire amount of the filtrate was stored in a separate container. The above procedure was repeated until the electrical conductivity became 8 mS / cm or less, and the amount of washing water used until the electrical conductivity became 8 mS / cm or less was measured and recorded as the amount of washing water.
[0084] Amount of phosphorus dissolved during cleaning The amount of P in the filtrate collected in a separate container was quantified using an ICP emission spectrometer (ULTIMA2, manufactured by Horiba, Ltd.) The smaller the amount, the better the cleaning efficiency.
[0085] Evaluation of charge / discharge characteristics Using each Li3PO4 particle shown in Table 3 as a raw material, an olivine-type lithium phosphate-based positive electrode material was manufactured by a conventional method, and a positive electrode for a lithium ion secondary battery was manufactured. Specifically, the olivine-type lithium phosphate-based positive electrode material, acetylene black, and polyvinylidene fluoride were mixed in a weight ratio of 90:5:5, and N-methyl-2-pyrrolidone was added to this and thoroughly kneaded to prepare a positive electrode slurry. The positive electrode slurry was applied to a current collector made of aluminum foil with a thickness of 20 μm using a coater, and vacuum dried at 80 ° C for 12 hours. Thereafter, it was punched into a disk shape of φ14 mm and pressed with a hand press at 16 MPa for 2 minutes to form a positive electrode. Next, a coin-type lithium ion secondary battery was constructed using the above positive electrode. A lithium foil punched to φ15 mm was used for the negative electrode. The electrolyte was a mixture of ethylene carbonate and ethyl methyl carbonate in a volume ratio of 1:1, in which LiPF6 was dissolved at a concentration of 1 mol / L. The separator was a well-known one, such as a polymer porous film such as polypropylene. These battery components were assembled and housed in an atmosphere with a dew point of -50°C or less by a conventional method, to produce a coin-type lithium ion secondary battery (CR-2032). A charge / discharge test at a constant current density was carried out using the manufactured lithium ion secondary battery. The charging conditions were a constant current charge of 0.2 CA (34 mAh / g) and a voltage of 4.5 V. The discharging conditions were a constant current discharge of 0.2 CA or 3 CA and a cut-off voltage of 2.0 V. The temperature was 30°C in all cases. The results are shown in Table 3, including the physical properties of each Li3PO4 particle and the filtration conditions used to obtain the particles.
[0086] [Table 1]
[0087] [Table 2]
[0088] [Table 3]
Claims
1. Li using a solution X discharged when obtaining an olivine-type lithium phosphate-based positive electrode material from a reaction mixture obtained by subjecting raw material compounds to a hydrothermal reaction. 3 P.O. 4 A method for producing particles, comprising the steps of: The following steps (I) to (IV): (I) A step of adding lithium carbonate and sulfuric acid, or lithium carbonate, lithium sulfate, and sulfuric acid to a solution X having a lithium ion content of 1000 mg / L to 20000 mg / L, to obtain a mixed solution A having a lithium ion content of 5000 mg / L to 30000 mg / L and a sulfuric acid content of 0.52 mol to 1.00 mol per 1 mol of lithium ion. (II) A step of subjecting the obtained mixed liquid A to a bubbling treatment with an inert gas to obtain a mixed liquid B. (III) A step of dropping a mixed solution C containing a phosphoric acid compound and an alkali compound into the obtained mixed solution B to obtain a mixed solution D having a lithium content of 2.7 mol to 3.3 mol per mol of phosphorus and a content of the alkali compound of 1.6 mol to 2.2 mol per mol of sulfuric acid. (IV) The resulting mixture D is subjected to solid-liquid separation to obtain Li 3 P.O. 4 Process for obtaining particles Li for obtaining an olivine-type lithium phosphate-based positive electrode material 3 P.O. 4 A method for producing particles.
2. The method according to claim 1, wherein the dropping speed of the mixed solution C in the step (III) is 10 to 100 minutes in terms of the time required for dropping the entire amount of the mixed solution C into the mixed solution B. 3 P.O. 4 A method for producing particles.
3. The Li according to claim 1 or 2, wherein the inert gas in the bubbling treatment in step (II) is nitrogen, argon, or helium. 3 P.O. 4 A method for producing particles.
4. In the solid-liquid separation in step (IV), a filter press, a centrifugal filter, or a vacuum filter is used, and the obtained Li 3 P.O. 4 The Li ion ... 3 P.O. 4 A method for producing particles.
5. The Li according to any one of claims 1 to 4, wherein the total amount of inert gas blown in the bubbling treatment in step (II) is 0.5 to 15 in terms of the ratio of the total volume of the blown inert gas to the volume of the mixed liquid A (total volume of inert gas / volume of the mixed liquid A). 3 P.O. 4 A method for producing particles.
6. The Li-based mixture according to any one of claims 1 to 5, wherein the phosphorus content in the mixed solution C used in the step (III) is 10,000 ppm to 60,000 ppm, and the alkali compound content is 2.7 mol to 3.6 mol per mol of phosphoric acid. 3 P.O. 4 A method for producing particles.
7. Li 3 P.O. 4 The particles have the formula (X): Li a Mn b Fe c M x P.O. 4 (wherein M represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd; and a, b, c, and x represent numbers that satisfy 0<a≦1.2, 0.3≦b≦1.2, 0.2≦c≦1.2, and 0≦x≦0.3, and a+(valence of Mn)×b+(valence of Fe)×c+(valence of M)×x=3.) 3 P.O. 4 A method for producing particles.
8. The solution X used in the step (I) is a solution containing the following steps (i) to (ii): (i) Li 3 P.O. 4 A step of adding and mixing a metal source that includes an iron compound and a manganese compound and may also include a metal (M) compound (M represents one or more elements selected from Mg, Al, Ti, Cu, Zn, Nb, Co, Ni, Ca, Sr, Y, Zr, Mo, Ba, Pb, Bi, La, Ce, Nd, and Gd) to the particles, and then subjecting the mixture to a hydrothermal reaction to obtain a reaction mixture. (ii) A step of separating the solution containing unreacted Li ions from the reaction mixture obtained in step (i) to obtain an olivine-type lithium phosphate-based positive electrode material. The Li according to claim 7, wherein the Li ion is a solution containing unreacted Li ions separated in step (ii) when an olivine-type lithium phosphate-based positive electrode material represented by formula (X) is obtained by passing through the above steps. 3 P.O. 4 A method for producing particles.
Citation Information
Patent Citations
Manufacturing method of electrode material, recovery method for lithium, positive electrode material, electrode, and battery
JP2008066019A
Manufacturing method for electrode material and recovery method for lithium phosphate
JP2020047514A
Method of manufacturing composite oxide
JP2020100555A